Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Co-precipitation technique to prepare BiTaO4 powders - Muthurajan, H.; Gupta, U. N.; Rituraj, B.; Rao, N. Koteswara; Pradhan, Sivaram; Radha, R.; Ravi, V. (Materials Letters, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure ultrafine single phase BiTaO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. This precursor, on heating at 600 degrees C, produced product phase. This is the lowest temperature for the formation of BiTaO4 phase so far reported in the literature. For comparison BiTaO4 powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: BiTaO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction